PEMIKIRAN DAN PENDIDIKAN SUFISTIK DALAM KITAB ADAB SULUK AL-MURID KARYA AL-HABIB ABDULLAH IBN 'ALAWI AL-HADDAD: (Sufistic Thought and Education in the Book of Adab Suluk Al-Murid by Al-Habib Abdullah ibn 'alawi Al-Haddad) - Fikri Maulana; Umar Agil Husaini (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2024)
Humans not only have a physical dimension, but also a spiritual dimension which in Islam is seen as a very important and determining dimension. So, in the modern era which prioritizes the external dimension and distances itself from the spiritual dimension, it is necessary for human efforts to continue to explore their inner self about themselves and all their possibilities. Like two sides of a coin, the outer dimension and the spiritual dimension cannot be separated, they are interrelated with one another. This article aims to explain Sufistic thought and education which seeks to provide Islamic treasures in the midst of the modern era which is completely individualist and materialist. This research is a literature research study, because the data collected focuses on Sufistic thought and education contained in the book Adab Suluk Al-Murid by Al-Habib Abdullah Ibn 'Alawi Al-Haddad. The data analysis used in this research uses a descriptive qualitative approach and analyzes it using a thematic approach. This article concludes that a human being needs to go through the stages in Adab Suluk Al-Murid by Al-Habib Abdullah Ibn 'Alawi Al-Haddad, there are 17 stages. However, in this article only 9 stages are presented, including: (1) Strong awareness, (2) Correct repentance, (3) Cleanse the heart, and (4) Refrain from committing sins.